1999
DOI: 10.1097/00006123-199902000-00073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ebselen on Contractile Responses in Perfused Rabbit Basilar Artery

Abstract: Ebselen suppressed ET-1-induced contraction and synergetic interaction between oxyhemoglobin and ET-1, where free radical formation was involved. These effects may result from modification of the intracellular regulatory system including protein kinase C, as well as from protection against free radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Ebselen has since been demonstrated to exhibit some beneficial effects on neurons, and provide some protection against ischemic insults. 3,4,13,20,27,28) Some evidence has been found showing that ebselen protects neurons against ischemic brain injury, but the mechanisms that account for the effects of this antioxidant remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Ebselen has since been demonstrated to exhibit some beneficial effects on neurons, and provide some protection against ischemic insults. 3,4,13,20,27,28) Some evidence has been found showing that ebselen protects neurons against ischemic brain injury, but the mechanisms that account for the effects of this antioxidant remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This selenium compound mimics the reactivity of glutathione peroxidase, reacting rapidly with peroxynitrite (k ϭ 2 ϫ 10 6 M Ϫ1 s Ϫ1 , pH Ն 8, 25 °C (90)) and being reduced back to its original form by glutathione. Experiments in clinical trials on ebselen have shown important plasma concentration of the drug ranging from 10 M at 2 h after administration to a baseline level of 5.1 M after 7 days oral administration of a daily dose of 400 mg (91). Under these conditions, k[T] is 10Ϫ20 s Ϫ1 .…”
Section: Box 1 Diffusion As a Kinetic Contendermentioning
confidence: 99%
“…Similar considerations may be apply to the synthetic compound ebselen [2-phenyl-1,2-benzisoselenazol-3-(2H)one], a lipid soluble selenium compound that exhibits glutathione peroxidase-like activity, which reduce peroxynitrite by two-electrons with a significant rate constant of 2 × 10 6 M −1 s −1 [143]. Experimental models after drug administration have determined ebselen plasma concentrations in the range of 5–10 μM, which represents a k T [T] value ~ 10–20 s −1 and could account for the reported protective effects of ebselen in several models of inflammation and reperfusion injury mediated by peroxynitrite [21,144,145,146]. Other organo selenium compounds were also reported to react with peroxynitrite.…”
Section: Modulation Of the Steady State Concentration Of Peroxynitmentioning
confidence: 99%